Parallel initial-value algorithms for singularly perturbed boundary-value problems - Gasparo, M. G.; Macconi, M. (Journal of optimization theory and applications, 1992)
Parallel algorithms for computing asymptotic approximations to the solutions of many singularly perturbed boundary-value problems are considered. Numerical techniques, called parallel-initial-value methods, are proposed which permit several natural computation decompositions into independent tasks. The number of disposable independent processors is taken into account to design suitable parallel schemes. The reliability and performance of the proposed schemes are demonstrated using a CRAY Y-MP 8/432 multiprocessor. (O.G.)